An Areal Assessment of Subseafloor Carbon Cycling in Cold Seeps and Hydrate-Bearing Areas in the Northern South China Sea - Yanping Zhang; Min Luo; Yu Hu; Hongbin Wang; Duofu Chen (Geofluids)
Gas hydrates, acting as a dynamic methane reservoir, store methane in the form of a solid phase under high-pressure and low-temperature conditions and release methane through the sediment column into seawater when they are decomposed. The seepage of methane-rich fluid (i.e., cold hydrocarbon seeps) fuels the chemosynthetic biota-inhabited surface sediments and represents the major pathway to transfer carbon from sediments to the water column. Generally, the major biogeochemical reactions related to carbon cycling in the anoxic marine sediments include organic matter degradation via sulfate reduction (OSR), anaerobic oxidation of methane (AOM), methanogenesis (ME), and carbonate precipitation (CP). In order to better understand the carbon turnover in the cold seeps and gas hydrate-bearing areas of the northern South China Sea (SCS), we collected geochemical data of 358 cores from published literatures and retrieved 37 cores and corresponding pore water samples from three areas of interest (i.e., Xisha, Dongsha, and Shenhu areas). Reaction-transport simulations indicate that the rates of organic matter degradation and carbonate precipitation are comparable in the three areas, while the rates of AOM vary over several orders of magnitude (AOM: 8.3-37.5 mmol·m-2·yr-1 in Dongsha, AOM: 12.4-170.6 mmol·m-2·yr-1 in Xisha, and AOM: 9.4-30.5 mmol·m-2·yr-1 in Shenhu). Both the arithmetical mean and interpolation mean of the biogeochemical processes were calculated in each area. Averaging these two mean values suggested that the rates of organic matter degradation in Dongsha (25.7 mmol·m-2·yr-1) and Xisha (25.1 mmol·m-2·yr-1) are higher than that in Shenhu (12 mmol·m-2·yr-1) and the AOM rate in Xisha (135.2 mmol·m-2·yr-1) is greater than those in Dongsha (27.8 mmol·m-2·yr-1) and Shenhu (17.5 mmol·m-2·yr-1). In addition, the rate of carbonate precipitation (32.3 mmol·m-2·yr-1) in Xisha is far higher than those of the other two regions (5.3 mmol·m-2·yr-1 in Dongsha, 5.8 mmol·m-2·yr-1 in Shenhu) due to intense AOM sustained by gas dissolution. In comparison with other cold seeps around the world, the biogeochemical rates in the northern SCS are generally lower than those in active continental margins and special environments (e.g., the Black sea) but are comparable with those in passive continental margins. Collectively, ~2.8 Gmol organic matter was buried and at least ~0.82 Gmol dissolved organic and inorganic carbon was diffused out of sediments annually. This may, to some extent, have an impact on the long-term deep ocean carbon cycle in the northern SCS.